Investigating of the effect of using bagasse and isocyanate adhesive on the 3-layer particleboard manufacturing - Kazem Dost hosseini (Regional Information Center for Science and Technology (RICeST), 2011)
In this research the physical and mechanical properties of 3-layer particleboard manufactured by bagasse and forest wood particles have been studied. The amount of raw material and the type of adhesive were variation factors. First the effect of raw material on physical and mechanical properties has been evaluated in the six treatments. 60-40% and 80-40% treatments (bagasse-wood particles), regarding to bending strength, modulus of elasticity, internal bending strength, water absorption and thickness swelling after 2 & 24 hours soaking in water, have been selected as optimum treatments. Then the effect of types of adhesive on optimum treatments has been evaluated. The achieved results show that the particleboards manufactured by isocyanate adhesive have the highest MOE and lowest water absorption and thickness swelling after 2 & 24 hours soaking in water. In this research, according to the results of analysis of variance and the interception effect of  raw material and type of adhesive on physical & mechanical properties of particleboards, 80-20% treatment (bagasse-wood particles) with isocyanate adhesive have been selected as preferable treatment